THE INFLUENCE OF BRAND AWARENESS AND PERCEIVED QUALITY ON REPURCHASE INTENTION: BRAND LOYALTY AS INTERVENING VARIABLE (CASE STUDY AT KOPI SOE BRANCH OF PANAKKUKANG MAKASSAR) - Regina Tuinesia; J. E. Sutanto; Michael Ricky Sondak (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Abstract: The study entitled “The Influence of Brand Awareness and Perceived Quality on Repurchase Intention: Brand Loyalty as Intervening Variable (Case Study at Kopi Soe Branch of Panakkukang Makassar) has seven research objectives, namely: (1) Knowing the effect of brand awareness on brand loyalty, ( 2) Knowing the effect perceived quality on brand loyalty, (3) Knowing the effect of brand awareness on repurchase intention, (4) Knowing the effect of perceived quality on repurchase intention, (5) Knowing the effect of brand loyalty on repurchase intention, (6) Knowing brand loyalty mediates the effect of brand awareness on repurchase intention, (7) Knowing brand loyalty mediates the effect of perceived quality on repurchase intention. Kopi Soe Branch of Panakkukang Panakkukang Makassar is a business engaged in beverages that offers local coffee. This research uses quantitative methods. The population in this study was the consumers of Kopi Soe Branch of Panakkukang Makassar who made transactions for the last six months. The sample in this study amounted to 130 respondents. Data was collected through the distribution of questionnaires distributed online using a google form. In this study, the data was processed using Smart PLS 3.0. The results of this study are: (1) Brand awareness has a significant effect on brand loyalty, (2) Perceived quality has a significant effect on brand loyalty, (3) Brand awareness has a significant effect on repurchase intention, (4) Perceived quality has no significant effect on repurchase intention, (5) Brand loyalty has a significant effect on repurchase intention, (6) Brand loyalty has a significant effect in mediating brand awareness on repurchase intention, (7) brand loyalty has a significant effect on mediating perceivd quality on repurchase intention. Keywords: Brand Awareness, Brand Loyalty, Perceived Quality, Repurchase Intention.